Forty‐eight weeks of statin therapy for type 2 diabetes mellitus patients with lower extremity atherosclerotic disease: Comparison of the effects of pitavastatin and atorvastatin on lower femoral total plaque areas - Zhou, Xieda; Wu, Liting; Chen, Yan; Xiao, Huangmeng; Huang, Xiaoyu; Li, Yanbing; Xiao, Haipeng; Cao, Xiaopei (Journal of diabetes investigation, 2021)
Aims/Introduction Type 2 diabetes mellitus is correlated with systemic atherosclerosis. Statin therapies have been proved to reduce low‐density lipoprotein cholesterol (LDL‐C) level, protecting type 2 diabetes mellitus patients from cardiovascular events. Recently, more interest has been focused on the regression of lower extremity atherosclerotic disease (LEAD) for the potential prevention of amputation. However, the effects of pitavastatin and atorvastatin on LEAD in type 2 diabetes mellitus patients have not been directly compared. Materials and Methods This study compared the effects of pitavastatin and atorvastatin on femoral total plaque areas (FTPA), and lipids and glucose metabolism in type 2 diabetes mellitus patients with elevated LDL‐C level and LEAD. Type 2 diabetes mellitus patients with LDL‐C level >2.6 mmol/L and LEAD were randomly assigned to receive either pitavastatin 2 mg/day or atorvastatin 10 mg/day for 48 weeks. FTPA were measured at baseline and the end of the study. Levels of glucose and lipids profile were measured periodically. The efficacy was evaluated in 63 patients. Results The percentage change in FTPA measurements was similar between the pitavastatin group and atorvastatin group (−17.79 ± 21.27% vs −14.34 ± 16.33%), as were the changes in LDL‐C (−44.0 ± 18.0% vs −40.3 ± 18.2%) and triglyceride (17.6 ± 20.0% vs 16.2 ± 17.0%). However, the level of high‐density lipoprotein cholesterol was significantly higher in the pitavastatin group compared with the atorvastatin group after 48 weeks of treatment (12.9 ± 10.3% vs 7.2 ± 11.7%, P < 0.05). There were no significant differences between groups for the measurements of glucose metabolism. Conclusion In type 2 diabetes mellitus patients with elevated LDL‐C level and LEAD, 48 weeks of treatment with either pitavastatin or atorvastatin was associated with significant regression of FTPA. Pitavastatin treatment resulted in a significantly higher high‐density lipoprotein cholesterol level compared with atorvastatin treatment. Forty‐eight weeks of treatment with either pitavastatin or atorvastatin was associated with significant regression of femoral total plaque areas. However, pitavastatin treatment resulted in a significantly higher high‐density lipoprotein cholesterol level compared with atorvastatin treatment. It seemed that pitavastatin might be superior in the control of dyslipidemia in diabetes patients.